Inovasi dan Prosedur Sistematis Pengembangan Bahan Ajar pkn Berorientasi LOTS, MOTS, dan HOTS : Strategi Mengintegrasikan Nilai-Nilai Pancasila dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Moulana, Mohammad Riefyal; Ardiyanti, Vivin; Qubro, Nia Aulia Khadijatul; Mauluah, Luluk (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
Civic Education in the 21st century requires innovative teaching materials that develop higher order thinking skills while integrating Pancasila values. The problem is the lack of hierarchically designed civic education materials based on LOTS, MOTS, and HOTS to enhance elementary students' critical thinking. This research aims to develop systematic procedures for preparing civic education materials oriented toward LOTS-MOTS-HOTS that integrate Pancasila values to improve elementary students' critical thinking abilities. The research method uses a qualitative approach with systematic literature review from Scopus, ERIC, Google Scholar, and Garuda databases for 2015-2025. Results show civic education materials need hierarchical design from LOTS for basic understanding, MOTS for concept application, to HOTS for analysis and evaluation. Pancasila values integration at each cognitive level effectively builds character while sharpening critical thinking. Development procedures include needs analysis, tiered objective formulation, contextual material preparation, and continuous evaluation. It is concluded that innovative civic education materials oriented toward LOTS-MOTS-HOTS integrated with Pancasila values are effective strategies for improving students' critical thinking. Teachers are recommended to apply this systematic procedure in designing contextual and meaningful civic education materials.